Singing the crusades : French and Occitan lyric responses to the crusading movements, 1137-1336 - Paterson, Linda M. (D.S. Brewer, 2018)
"The crusading movements provoked a vast and diverse mass of reactions in the medieval West. While Latin sources provide official versions of its preaching, organisation and events, the vernacular lyrics of the troubadours and trouvères present a secular perspective, through a cornucopia of on-the-spot responses in France, Occitania, Italy, the Iberian Peninsula, Cyprus, Syria and Greece. This book constitutes the first comprehensive, modern analysis of Old French and Occitan lyric texts relating to the crusades. It brings out their full range, from propaganda for the crusades, to criticisms of crusading and crusaders through vituperation, humour or cynicism, to their use as a pretext for political or personal wrangling. It also shows how they shed light on many aspects of medieval life, among them chivalric and courtly values (often in tension with clerical ones), regional politics, sexual behaviour, personal experiences of crusading and captivity, the complex interaction of Christians, Greeks and Muslims, and bafflement in the face of failure and God's imponderable purposes"--Back cover image.